2019
DOI: 10.1111/nyas.14227
|View full text |Cite
|
Sign up to set email alerts
|

Spatial regulation of GPR64/ADGRG2 signaling by β‐arrestins and GPCR kinases

Abstract: Mechanisms of activation, signaling, and trafficking of adhesion G protein–coupled receptors (aGPCRs) have remained largely unknown. Several aGPCRs, including GPR56/ADGRG1 and GPR64/ADGRG2, show increased activity in the absence of their N‐terminal fragment (NTF). This constitutive signaling is plausibly caused by the binding of extracellular N‐terminal 15–25 amino acid–long tethered agonist to extracellular domains of the cognate aGPCRs. To test the role of NTF and tethered agonist in GPR64 signaling and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 48 publications
(73 reference statements)
5
30
1
Order By: Relevance
“…By applying our newly developed agonist VPM-p15, we further demonstrated that the arrestins could be recruited to ADGRG2 in an agonist-dependent manner. The small differences between previous results and ours regarding the p15-induced arrestin recruitment to wild-type ADGRG2 may be due to altered experimental methods with different sensitivities (24).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…By applying our newly developed agonist VPM-p15, we further demonstrated that the arrestins could be recruited to ADGRG2 in an agonist-dependent manner. The small differences between previous results and ours regarding the p15-induced arrestin recruitment to wild-type ADGRG2 may be due to altered experimental methods with different sensitivities (24).…”
Section: Discussioncontrasting
confidence: 85%
“…In this study, we found that the ADGRG2-β (CTF fragment) showed higher constitutive activity for arrestin recruitment compared to that of the full-length ADGRG2 (Supplemental Figure 1E-F). Consistently, a recent study reported that △NTF and P622 mutants of ADGRG2 interacted with β-arrestin1 and β-arrestin2, which induced constitutive internalization of ADGRG2 in steady states (24). Therefore, the arrestin recruitment to ADGRG2 might be strengthened by activation of the ADGRG2 via Stachel sequence interaction.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It was found that the TM1 N-terminal stalk sequence consisting of ~20 residues behaved as a tethered-peptide-agonist and dramatically activated AGPCRs. Deletion of tethered agonist residues dramatically lowered receptor activities in vitro, as shown for ADGRG1, ADGRG2 (GPR64), ADGRG6, and ADGRD1 (GPR133), and ADGRF1 (21,22,40,41). Partial deletion of the zebrafish ADGRG6 tethered agonist resulted in a puffy ear phenotype and impairment of nerve cell myelination, essentially phenocopying the fish model deletion of the ADGRG6 CTF (22,42).…”
Section: Agonism (Tethered-peptide Agonism)mentioning
confidence: 73%
“…These studies established ADGRG2 as a novel gene responsible for a specific subtype of obstructive azoospermia. The molecular mechanism of X-linked CBAVD remains uncertain, although a regulation of fluid reabsorption by G-protein-dependent CFTR coupling and β-arrestin-dependent receptor internalization has been postulated (Zhang et al 2018 ; Azimzadeh et al 2019 ).…”
Section: Obstructive Azoospermiamentioning
confidence: 99%